Ответы и объяснения

  • fou
  • ученый
2013-01-12T22:26:14+04:00

1. \lim_{n \to \infty} \frac{2^{2-n}-3^{2-n}}{2^{1-n}-3^{1-n}}= \lim_{n \to \infty} \frac{9\cdot 2^{n}-4\cdot 3^{n}}{3\cdot 2^{n}-2\cdot 3^{n}}=\\=9 \lim_{n \to \infty} \frac{ 2^{n}}{3\cdot 2^{n}-2\cdot 3^{n}}-4 \lim_{n \to \infty} \frac{ 3^{n}}{3\cdot 2^{n}-2\cdot 3^{n}}=\\=9 \lim_{n \to \infty} \frac{1}{3-2^{1-n}\cdot 3^{n}}-4 \lim_{n \to \infty} \frac{1}{3^{1-n}\cdot 2^{n}-2}=\\=\frac{9}{\lim_{n \to \infty} (3-2^{1-n}\cdot 3^{n})}-\frac{4}{\lim_{n \to \infty} (-2+3^{1-n}\cdot 2^{n})}

Применяем правило Лопиталя к неопределенности:

\frac{9}{\lim_{n \to \infty} (3-\frac{\frac{d(2\cdot 3^{n})}{dn}}{\frac{d2^{n}}{dn}})}-\frac{4}{\lim_{n \to \infty} (-2+\frac{\frac{d(3\cdot 2^{n})}{dn}}{\frac{d3^{n}}{dn}})}}=\\=\frac{9}{\lim_{n \to \infty} (3-\frac{2^{1-n}3^{n}ln(3)}{ln(2)})}-\frac{4}{\lim_{n \to \infty} (-2+\frac{2^{n}3^{1-n}ln(2)}{ln(3)})}=\\=\frac{9}{\lim_{n \to \infty} (3-\frac{(\frac{3}{2})^{n}ln(9)}{ln(2)})}-\frac{4}{\lim_{n \to \infty} (-2+\frac{(\frac{2}{3})^{n}ln(8)}{ln(3)})}=\\

=\frac{9}{ (3-\frac{ln(9)\lim_{n \to \infty}((\frac{3}{2})^{n})}{ln(2)})}-\frac{4}{ (-2+\frac{ln(8)\lim_{n \to \infty}((\frac{2}{3})^{n})}{ln(3)})}=\\=\frac{9}{ (3-\frac{ln(9)\lim_{n \to \infty}((\frac{3}{2})^{n})}{ln(2)})}-\frac{4}{ (-2+\frac{ln(8)(\frac{2}{3})^{\lim_{n \to \infty} n}}{ln(3)})}= 0+2=2